Potential antidiabetic properties of G. mangostana Linn. on Streptozotocin-induced diabetic rats - Bakhtiar, M. Taher; Tengku Zakaria, Tengku Muhamad Faris Syafiq; Azad, Abul Kalam (2014)

(untitled)
Aim: The aim of the study was to evaluate the biochemical effects and histopathological alterations of the ethanolic extracts of G. mangostana pericarps (GME) on STZ-induced diabetic rats. Methods: Oral administration of GME at doses of 50, 100 and 200mg/kg b.w. were given to STZ-induced diabetic and normoglycaemic albino rats. The serum biochemical parameters, enzymatic analysis and histopathological alterations were examined and compared to reference standard hypoglycamic drug, glibenclamide. Analytes including blood glucose, liver transminases viz. alanine aminotransferase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALT); lipid profile included triglycerides (TG), total cholesterol (TC), High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL) and Very Low Density Lipoprotein (VLDL); creatinine, urea and total protein were checked using standard test kits and reagents. Histological changes in the liver, kidney and pancreas of the animals were also examined. Results: The results obtained revealed a significant reduction of glucose level in GME with doses of 100mg/kg (p<0.001) and 200mg/kg (p<0.001) compared to 50mg/kg. Total cholesterol, serum triglyceride, LDL, VLDL, urea and creatinine were reduced in the treatment group while total protein contents and HDL level mildly elevated. Histological assessment revealed a reduction in lesions associated with diabetic state in STZ-induced rats.